Waterfowl wintering, resting and breeding areas of the south-west Caspian lowlands - Ferguson, David A (Wildfowl, 1972)
The waterfowl and wetlands of the south-west Caspian lowlands were intensively surveyed over a period of three years from January 1967 through April 1970. Factors affecting management of the waterfowl and the overall ecology of the region are discussed. It is concluded that a number of species use the area as a refuelling ground during passage migration and a few remain to nest in small numbers. The importance of the region as a wintering ground is dependent on the number, proximity to others, and degree of protection afforded the individual wetland habitats, and the entire area is severely threatened by man-caused disturbance and development projects.